PENERAPAN KONSEP TRI KAYA PARISUDHA DALAM MENINGKATKAN KINERJA PRGAWAI (STUDI PADA RUMAH SAKIT BALIMED) - I Putu Agus Adnyana; Komang Reni Pramita Dewi (Jurnal Inovasi Penelitian, 2022)
This study aims to describe the application of Tri Kaya Parisudha in the implementation of work in order to improve employee performance at BaliMéd Hospital. This study uses a qualitative approach with interviews as a data collection technique. Informants in this study were employees of Balimed Hospital. The analytical technique used in this research is descriptive analysis. The results show that the application of the Tri Kaya Parisudha concept at BaliMéd Hospital is considered quite effective in improving employee performance where the application of the Tri Kaya Parisudha concept in the management function is the implementation of the Tri Kaya Parisudha concept in accordance with the previously planned program. The results showed that the application of the Tri Kaya Parisudha concept was able to improve employee performance where the Tri Kaya Parisudha concept could be used as a basis for reference and the driving force for motivation, attitudes and actions that were in line with the organization's vision and mission in providing health services to the community.